Kerangka Konseptual Pemilihan Materi Pembelajaran Bahasa dan Sastra Jepang Guna Pencapaian Kompetensi Komunikatif Antarbudaya (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2016)
In conceptualizing learning material, attention needs to be paid to the needs and the environment of the learners, and in addition to the socio cultural systems as the third element that greatly affect a person's perceptual activity of the culture and intercultural communication. The conceptual frame work of intercultural learning materials also need to considerate intercultural awareness, intellectual understanding, and intercultural skills. Byram’s four learning components, namely: language learning, language awareness, culture awareness, and culture experience can also be integrated in intercultural literary language learning materials. Through of this conceptual frame work, an intercultural communicative potential of Indonesia-Japan are expected to be grown.